2007
DOI: 10.1016/j.jacc.2007.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Surface CD62P and CD63, Mean Platelet Volume, and Soluble/Platelet P-Selectin as Indexes of Platelet Function in Atrial Fibrillation

Abstract: There is a degree of excess of platelet activation in AF compared with "healthy control subjects," but no significant difference between AF patients and "disease control subjects" in sinus rhythm. Platelet activation may differ according to the subtype of AF, but this is not in excess of the underlying comorbidities that lead to AF. Platelet activation in AF may be due to underlying cardiovascular diseases, rather than due to AF per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 52 publications
(39 reference statements)
3
72
0
1
Order By: Relevance
“…Within 12 hours of arrhythmia onset patients with paroxysmal AF have detectable P-selection levels (18). While excess platelet activation in AF compared with healthy control subjects is significant, no significant difference between AF patients and disease control subjects in sinus rhythm was detected (7). When considering the findings from the study of Choudhury et al we performed the present analysis and found that new-onset POAF is independently associated with HAPR in patients following CABG.…”
Section: Commentmentioning
confidence: 69%
See 2 more Smart Citations
“…Within 12 hours of arrhythmia onset patients with paroxysmal AF have detectable P-selection levels (18). While excess platelet activation in AF compared with healthy control subjects is significant, no significant difference between AF patients and disease control subjects in sinus rhythm was detected (7). When considering the findings from the study of Choudhury et al we performed the present analysis and found that new-onset POAF is independently associated with HAPR in patients following CABG.…”
Section: Commentmentioning
confidence: 69%
“…Other possible mechanisms that have been proposed include inflammatory response reaction (5) and neuroendocrine activation (6). Increased expression of platelet activation markers has been shown to be associated with AF (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the quantification of platelet abnormalities can be performed using a wide variety of measures, such as platelet volume, aggregometry (Gabassov et al, 1989), excretion of metabolites (FitzGerald et al, 1988), flow cytometry (Corash, 1990) to detect various platelet antigens, and by the measurement of increased plasma levels of platelet products, such as platelet factor 4, beta thromboglobulin (Chen &Wu, 1980;Ikeda et al,1997) , the soluble adhesion molecule P-selectin (Blann et al, 1997),soluble CD40L (Choudhury et al,2007) and matrix metalloproteinase-1 (Martin et al,2003) (Table 2). However, some measures (such as platelet volume) are less useful or practical.…”
Section: The Assessment Of Platelet Activationmentioning
confidence: 99%
“…The mechanism by which the risk for embolic cerebral events is enhanced is not fully established. Sporadic reports indicate that AF is associated with increased levels of circulating platelet-derived substances such as soluble p-selectin [1,2]. It has been hypothesized that platelet alterations are signs of underlying cardiovascular co morbidity [3].…”
Section: Introductionmentioning
confidence: 99%